Design of Biodiesel Reactor Using Nanocatalyst ZnO From Castor Oil - Ranggaweny Al-Ghani; Asep Bayu Dani Nandiyanto; Teguh Kurniawan (Metrotech (Journal of Mechanical and Electrical Technology), 2023)
Mass transfer during the reaction process is limited in industrial biodiesel manufacture. Therefore, to overcome this problem, a reactor from castor oil transesterified using ZnO nanocatalyst was designed. ZnO can be used as a catalyst for biodiesel production due to the nature of ZnO which has high catalytic activity, low material costs and is environmentally friendly. This study aims to design a design for the manufacture of zinc oxide (ZnO) nanocrystals using a continuous stirred tank reactor (CSTR) reactor. By giving data on incoming feedstock and product flow produced by the reactor, mass balance calculations were used in this study as a benchmark to determine whether the reactor was operating appropriately. Additionally, using Microsoft Excel, manual calculations were done for the reactor design and agitator design employed in the reactor. According to calculations used in reactor design, the reactor has a volume of 1967.78 liters, a vessel diameter of 44.77 inches, a height of 19.25 inches, and a thickness of 44.98 inches. The reactor is equipped in one stirrer with a power on a typical 10 hp agitator motor, turbulent agitator flow conditions exist.